Influence of sex and functional status on the value of serum steroid profiling in discriminating adrenocortical carcinoma from adrenocortical adenoma - Weng, Yan; Tang, Ju-Ying; Zhang, Xiao-Yun; Lin, Diao-Zhu; Guo, Ying; Liang, Ying; Wang, Lin; Zhou, Jing; Yan, Li; Lin, Tian-Xin; Zhang, Shao-Ling (Frontiers in Endocrinology, 2024)
Background: It is challenging for a clinician to distinguish adrenocortical carcinoma (ACC) from benign adrenocortical adenomas (ACA) in the early stage. This study explored the value of serum steroid profiling as a complementary biomarker for malignancy diagnosis ACC other than diameter, and explored the influence of sex and functional status on it.In this retrospective study, a matched cohort of patients diagnosed with either ACC or ACA based on histopathology was meticulously paired in a 1:1 ratio according to sex, age and functional status. Eight serum steroids including 11-deoxycortisol, 11deoxycorticosterone, progesterone, androstenedione, dehydroepiandrosterone (DHEA), dehydroepiandrosterone-sulfate (DHEAS), 17-hydroxyprogesterone and estradiol were quantified by liquid chromatography tandem mass spectrometry. We conducted a comparative analysis of clinical characteristics and serum steroid profiling between patients with ACC and ACA, with further subgroup analysis.The study examined 31 patients with ACC and 31 matched patients with ACA.Patients with ACC exhibited significantly larger tumor diameters, lower body mass index (BMI), and higher level of 11-deoxycortisol, progesterone, and androstenedione compared to those with ACA. 11-deoxycortisol was the only valuable index for discriminating ACC with ACA regardless of its functional status and sex. Progesterone, DHEA and DHEAS were higher in functional ACC group, not in non-functional ACC.Female ACC patients especially in post-menopausal female exhibited higher levels of androstenedione, not in male. The area under curve of tumor diameter, 11-deoxycortisol and BMI was 0.947 (95% CI 0.889-1.000), with the sensitivity of 96.8% and specificity of 90.3%.Serum steroid profiling serves as a helpful discriminative marker for ACC and ACA, with 11-deoxycortisol being the most valuable one. For other steroid hormones, consideration of sex differences and functional status is crucial.